2004
DOI: 10.1111/j.1751-1097.2004.tb00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Thylakoid‐associated Polyamines Adjust the UV‐B Sensitivity of the Photosynthetic Apparatus by Means of Light‐harvesting Complex II Changes

Abstract: The sensitivity of the photosynthetic apparatus to ultraviolet‐B (UV‐B) irradiation was studied in cultures of unicellular green alga Scenedesmus obliquus incubated in low light (low photosynthetically active radiation intensity [LL]) and high light (high photosynthetically active radiation intensity [HL]) conditions, treated or not with exogenous polyamines. Biochemical and physicochemical measurement showed that UV‐B radiation induces a decrease in the thylakoid‐associated putrescine (Put) and an increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In this context, PAs could act either as carbon/nitrogen reserves or as signal molecule(s) regulating senescence and probably sink-source relationships. Also, PAs are present in thylakoid membranes, PSII, and the lightharvesting complex (Kotzabasis et al, 1993b;Sfichi et al, 2004), suggesting a functional role in the photosynthetic activity during senescence or in the regulation of photoassimilate synthesis and/or partitioning between organs. PAs also inhibit ethylene biosynthesis and other degrative processes associated with senescence, including chlorophyll loss, increase in membrane leakage, and rise in RNAse and protease activities (Pandey et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, PAs could act either as carbon/nitrogen reserves or as signal molecule(s) regulating senescence and probably sink-source relationships. Also, PAs are present in thylakoid membranes, PSII, and the lightharvesting complex (Kotzabasis et al, 1993b;Sfichi et al, 2004), suggesting a functional role in the photosynthetic activity during senescence or in the regulation of photoassimilate synthesis and/or partitioning between organs. PAs also inhibit ethylene biosynthesis and other degrative processes associated with senescence, including chlorophyll loss, increase in membrane leakage, and rise in RNAse and protease activities (Pandey et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Kotzabasis et al (1993) reported that the main polyamines, putrescine, spermidine and spermine are associated with the thylakoid membranes and, especially, at the level of light-harvesting complex II as well as PSII complex. Several reports have attributed a key role of polyamines in the regulation of photosynthetic apparatus under adverse conditions like salinity and UV light (Demetriou et al 2007;Sfichi et al 2004). The EL reflects the damage of cell membranes.…”
Section: Polyamine Accumulation Induces Salt Tolerance In Tomato Planmentioning
confidence: 99%
“…A less known group of molecules called polyamines (PAs), which can be free in the cell or bound to thylakoid membranes of plants and algae, have been associated with repair or photoprotective functions during severe high light and UV stress (Sfichi-Duke et al, 2004), resembling functions of some stress proteins. The three major polyamines, putrescine (PUT), spermine (SPM) and spermidine (SPD) have been reported to have roles in many biological processes such as cell division, growth and senescence (Igarashi & Kashiwagi, 2000).…”
Section: Polyaminesmentioning
confidence: 99%